Prescription medication use of United States military service members by therapeutic classification - Knapik, Joseph J.; Trone, Daniel W.; Steelman, Ryan A.; Farina, Emily K.; Lieberman, Harris R. (Frontiers in Pharmacology, 2022)
Background: This cross-sectional study investigated the prevalence of, and factors associated with, filled 30 prescription medications (FPMs) among United States (US) service members (SMs). Methods: A 31 stratified random sample of active duty SMs from the Air Force, Army, Marine Corps, and Navy was 32 obtained from military workforce records. Participants (n=26,680) completed a questionnaire on 33 demographics, physical characteristics, and lifestyle factors and approved access to their FPM for the 34 previous 6 months. FPMs were obtained from the military Pharmacy Data Transaction Service that 35 included all prescription medications dispensed at military medical treatment facilities, abroad, at retail 36 pharmacies in the US, and/or through mail-order programs. Results: About two-thirds (65%) of SMs had 37 ≥1 FPM in the 6 month surveillance period. Central nervous system (CNS) agents had the highest 38 prevalence (41%), followed by anti-infective agents (20%), eye/ear/nose/throat preparations (20%), 39 gastrointestinal drugs (18%), autonomic drugs (17%), skin & mucous membrane agents (13%), 40 antihistamine drugs (12%), respiratory tract agents (12%) and cardiovascular drugs (9%). Among CNS 41 agents, overall prevalence of dispensed non-steroidal anti-inflammatory drug (NSAIDs) was 30%. The 42 odds of any FPM was independently associated with female gender, older age, higher body mass index, 43 former tobacco use (smoking and smokeless tobacco), lower alcohol consumption, and was highest 44 among Army, lowest among Marine Corps personnel. Conclusion: In this relatively young and 45 physically active population, dispensing of CNS agents was high, especially NSAIDs, but dispensing of 46 cardiovascular drugs was much lower compared to the general US population.